Case report: Primary immunodeficiency due to a novel mutation in CARMIL2 and its response to combined immunomodulatory therapy - Zhu, Yu; Ye, Lili; Huang, Hua; Xu, Xuemei; Liu, Yu; Wang, Jian; Jin, Yanliang (Frontiers in Pediatrics, 2023)
Capping protein regulator and myosin 1 linker 2 (CARMIL2) is necessary for invadopodia formation, cell polarity, lamellipodial assembly, membrane ruffling, acropinocytosis, and collective cell migration. CARMIL2 deficiency is a rare autosomal recessive disease characterized by dysfunction in naïve T-cell activation, proliferation, differentiation, and effector function and insufficient responses in T-cell memory. In this paper, we report a 9-year-old female patient with a novel pathogenic variant in CARMIL2 (c.2063C > G:p.Thr688Arg) who presented with various symptoms of primary immunodeficiencies including recurrent upper and lower respiratory infections, perioral and perineum papules, reddish impetiginized atopic dermatitis, oral ulcer, painful urination and vaginitis, otitis media, and failure to thrive. A missense mutation leading to insufficient CARMIL2 protein expression, reduced absolute T-cell and natural killer cell (NK cell) counts, and marked skewing to the naïve T-cell form was identified and indicated defective maturation of T cells and B cells. Following 1 year of multitargeted treatment with corticosteroids, hydroxychloroquine, mycophenolate mofetil, and thymosin, the patient presented with significant regression in rashes. CD4+ T-cell, CD8+ T-cell, and NK cell counts were significantly improved.